Discovery of Antitumor Active Peptides Derived from Peroxiredoxin 5. (6th September 2021) - Liu, Juanjuan; Zou, Sen; Zhang, Yan; Lin, Ru; Duan, Yanbo; He, Weiqing; Yang, Zhaoyong
Abstract: The peroxiredoxin 5 (PRDX5) is a member of peroxiredoxins with antitumor activity. However, as a recombinant protein, PRDX5 is restricted in clinic due to high cost and keeping high dose in medication. The alternative way is to explore the antitumor active fragments of PRDX5 for potential of peptide drugs. According to the sequence, crystal structure and enzyme function of PRDX5, seven peptides were designed and named as IMB‐P1∼7. The peptide IMB‐P1 (AFTPGCSKTHLPGFVEQAEAL) containing critical residue C47 exhibited antitumor activity similar to PRDX5 in vivo . Transcriptome analysis showed peptide IMB‐P1 could make influence on expression of multiple genes involved in tumorigenesis and deterioration. Besides, an important discovery is the down‐regulation of oxidation‐related genes. In CT26 cells, IMB‐P1 carried similar antitumor activity with increasing ROS level to intact PRDX5. The results demonstrated that peptide IMB‐P1 with easier synthesis from PRDX5 may serve as a promising antitumor candidate. Abstract : Fully functional fragment : Seven peptides were designed in accordance with the sequence, crystal structure, and enzyme function of PRDX5. The peptide IMB‐P1 (AFTPGCSKTHLPGFVEQAEAL) containing the critical residue C47 was found to retain similar antitumor activity as that of intact PRDX5 protein in vivo and in vitro .